2004
DOI: 10.1089/ten.2004.10.1180
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Apligraf in Acute Human Wounds

Abstract: Apligraf consists of bovine collagen dermis seeded with allogeneic male fibroblasts and keratinocytes. It is been shown to promote healing, but the length of persistence and pathological features have not been characterized previously in acute wounds. Forty-eight deep dermal wounds were created and Apligraf, a split-skin graft (SSG), or a dressing was applied. Biopsies of wounds were taken for immunohistochemical analysis and polymerase chain reaction was performed to detect the Y chromosome from Apligraf cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
93
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(96 citation statements)
references
References 58 publications
1
93
0
2
Order By: Relevance
“…There are reports of host immunogenic tolerance to allogeneic fibroblasts (Coulomb et al 1998) and their survival in the host up to three weeks (Morimoto et al 2005). Long-term preservation of allogeneic fibroblasts and their proliferation up to two months in the host without signs of immune rejection have also been reported (Sher et al 1983;Bell et al 1984;Eaglstein et al 1999;Hebda & Dohar 1999;Sandulache et al 2003;Griffiths et al 2004). However, porcine studies could not confirm allogeneic fibroblast survival beyond a 7-day time point ), nor could some clinical studies when allogeneic fibroblasts were transplanted onto burn wounds (Kolokol'chikova et al 2001).…”
Section: Dermo-epidermal (Composite) Skin Substitutesmentioning
confidence: 98%
See 1 more Smart Citation
“…There are reports of host immunogenic tolerance to allogeneic fibroblasts (Coulomb et al 1998) and their survival in the host up to three weeks (Morimoto et al 2005). Long-term preservation of allogeneic fibroblasts and their proliferation up to two months in the host without signs of immune rejection have also been reported (Sher et al 1983;Bell et al 1984;Eaglstein et al 1999;Hebda & Dohar 1999;Sandulache et al 2003;Griffiths et al 2004). However, porcine studies could not confirm allogeneic fibroblast survival beyond a 7-day time point ), nor could some clinical studies when allogeneic fibroblasts were transplanted onto burn wounds (Kolokol'chikova et al 2001).…”
Section: Dermo-epidermal (Composite) Skin Substitutesmentioning
confidence: 98%
“…Although this product does not cause immunological rejection, allogeneic cells of the construct do not survive after one to two months in vivo (Eaglstein et al 1999;Griffiths et al 2004). Hence, Apligraf, which was marketed initially as an organotypic skin substitute, can only be considered as a temporary bioactive dressing.…”
Section: Apligrafmentioning
confidence: 99%
“…Cryopreserved dermal substitutes appear to promote the same degree of re-epithelialization as native living substitutes (144). Several studies have indicated that allogeneic fibroblasts do not persist, at least in acute wounds (145). It is probable, therefore, that all these products serve more as biological dressings than as tissue replacements.…”
Section: Oral Autologous Grafts For Extra-oral Applicationsmentioning
confidence: 99%
“…Apligraf is considered a temporary dressing because the allogenic cells survive less than 2 months in vivo [58]. Disadvantages of Apligraf are that it cannot be used for fullthickness wounds, the shelf life is only 5 days, and it requires delicate handling.…”
Section: Skin Substitutes Containing Allogenic Live Fibroblastsmentioning
confidence: 99%